OPTIMAL PORTFOLIO FORMATION USING THE SINGLE INDEX MODEL (A STUDY ON IDXPROPERT STOCKS LISTED ON THE INDONESIA STOCK EXCHANGE FROM JANUARY 2020 TO DECEMBER 2024) - Dewi Hasrina; Anwar; Annisa Paramaswary Aslam; Anwar Ramli; Nurman (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to determine the formation of an optimal portfolio on IDXPROPERT stocks using the Single Index Model from January 2020 to December 2024. The research method used is quantitative research with a descriptive approach. The population in this study includes all IDXPROPERT stocks listed on the Indonesia Stock Exchange, and the research sample was determined using purposive sampling method. The data used in this study are secondary data collected through documentation techniques and then analyzed using the Single Index Model. The results show that from 64 stocks used as research samples, 7 stocks form the optimal portfolio. The stocks that form the optimal portfolio and the proportion of funds allocated to each stock are GMTD (2.95%), LPLI (2.65%), MKPI (6.36%), NIRO (71.59%), PAMG (1.15%), RISE (13.07%), and SATU (2.23%). From the formed optimal portfolio, the expected return for investors is 0.0052 or 0.52% with a risk of 0.0116 or 1.16%. This study also shows that the portfolio risk is smaller compared to the risk of each individual stock before being grouped into a portfolio. Additionally, the expected return of the portfolio is not significantly different from the expected return of individual stocks. This indicates that the use of the Single Index Model is effective in minimizing stock investment  risk through diversification, while maintaining a certain level of return.